Analisis Efektivitas Jalur Evakuasi Inklusif pada Kawasan Padat Penduduk Menggunakan Analisis Space Syntax - Septiansyah, Adeka; Agustiananda, Putu Ayu Pramanasari; Idham, Noor Cholis (IAI Nasional Laa Roiba Bogor, 2025)
The effectiveness of evacuation route is seen from the spatial configuration that shows the relationship between several spaces resulting in a spatial organization or structure in the form of circulation movement activities and interacting with each other. Research on this spatial configuration is very important to achieve effectiveness. The creation of effectiveness is very important because it is closely related to the effectiveness of inclusive evacuation. Kali Anyar Urban Village, which is located on the island of Java, is located in Tambora District, West Jakarta. A densely populated village that has a history of quite high fire disasters. Therefore, an analysis of the effectiveness of this evacuation route is very important. This research using a space syntax analysis technique by analyzing the spatial configuration using the DepthmapX application. The purpose is to determine the effectiveness of an inclusive evacuation route in Kali Anyar Urban Village, Jakarta. The measurement results show not good connectivity value (low), not good integration value (low), and not good Intelligibility value (low). The results from the analysis of the effectiveness of this evacuation route are formulated into an inclusive evacuation route in Kali Anyar Urban Village, Jakarta.